Exercise prehabilitation program for patients under neoadjuvant treatment for rectal cancer: A pilot study - Alejo, Lidia; Pagola-Aldazabal, Itziar; Fiuza-Luces, Carmen; Huerga, Daniel; de Torres, María; Verdugo, Ana; Ortega Solano, María; Felipe, José; Lucia, Alejandro; Ruiz-Casado, Ana (Journal of cancer research and therapeutics, 2019)
Context: Prehabilitation is emerging as a method of preparing patients physically and mentally for the often disabling effects of cancer treatment. Aims: This study aims to assess the feasibility and to explore the potential effects of a prehabilitation program consisting of educational physical exercise sessions in patients with rectal cancer undergoing neoadjuvant chemoradiotherapy treatment (NCRT). Settings and Design: This was a pilot study with 12 patients (3 males and 9 females, age 61 ± 7 years). Subjects and Methods: The program included six educational sessions of exercise during NCRT. Adherence to the intervention; quality of life (QoL); anxiety and depression; body mass index; physical fitness (peak oxygen uptake (VO2peak), handgrip and dynamic leg strength); and physical activity (PA) levels were measured. Statistical Analysis Used: Data are reported as the mean ± standard deviation or medians and interquartile ranges for questionnaire-derived data. Secondary outcome measures were compared using the nonparametric Wilcoxon test. The threshold P value for significance was calculated after correction for multiple comparisons using the Bonferroni method. Results: Adherence to the program was 64 of 72 possible exercise education sessions completed, i.e., 89%. We detected a trend toward a significant improvement in VO2peak after the intervention (P = 0.015), together with reduced scores for both depression (P = 0.017) and the QoL domain "emotional function" (P = 0.027). Mean levels of moderate to vigorous PA tended to increase after the exercise program (P = 0.091). Conclusions: Exercise might be an effective prehabilitation strategy for surgery during the period of NCRT.